Immunoglobulin G enzyme-linked immunosorbent assay using truncated nucleoproteins of Reston Ebola virus. - Ikegami, T. (Cambridge University Press, 2003)
We developed an immunoglobulin G (IgG) enzyme-linked immunosorbent assay (ELISA), using partial recombinant nucleoproteins (rNP) of Reston Ebola virus (EBO-R) and Zaire Ebola virus (EBO-Z). We examined the reaction of 10 sera from cynomolgus macaques naturally infected with EBO-R to each of the partial rNP in the IgG ELISA. All the sera reacted to the C-terminal halves of the rNP of both EBO-R and EBO-Z. Most of the sera reacted to the RdeltaC (amino acid (aa) 360-739), and Rdelta6 (aa 451-551) and/or Rdelta8 (aa 631-739) at a higher dilution than to the corresponding truncated rNPs of EBO-Z. The results indicate that this IgG ELISA is useful for detecting EBO-R specific antibody, and may have a potential to discriminate EBO-R infection from other subtypes.